Relation Between Social Support Received and Provided by Parents of Children, Adolescents and Young Adults With Cancer and Stress Levels and Life and Family Satisfaction - Melguizo-Garín, Anabel; Martos-Méndez, Mª José; Hombrados-Mendieta, Isabel; Ruiz-Rodríguez, Iván (Frontiers in Psychology, 2022)
Introduction The present study aims at analysing how social support received and provided by parents of children, adolescents and young adults (AYA) diagnosed with cancer, as well as their sociodemographic and clinical variables, affect those parents’ stress levels and life and family satisfaction. Materials and Methods A total of 112 parents of children and AYAs who had been diagnosed with cancer and who received treatment in Malaga participated in the study. In the study, participated all parents who voluntarily agreed to fulfil the questionnaire. The main inclusion criterion was that their child had cancer. Instruments used were Questionnaire on the Frequency of and Satisfaction with Social Support (QFSSS), Paediatric Inventory for Parents (PIP), Life Satisfaction Scale and Family Satisfaction Scale. Results In the mean difference analyses, male parents showed 3.38 (SD = 0.56) in social support received and female parents showed M = 3.08 (SD = 0.72). Conversely, in social support provided, female parents showed 3.22 and male parents showed M = 3.55 (p = 0.020). Significant differences were also found in family satisfaction, where female parents (M = 3.64) feel more satisfied than male parents (M = 3.06; p = 0.027). Parents of children aged between 0 and 14 years (M = 3.06) feel more stress than those parents of children aged 15–21 (M = 2.61; p = 0.021). The correlation analysis shows that there is a negative and significant relation between stress levels experienced by parents when facing different situations related to the child’s disease and both types of support, received r = −0.411, p < 0.001 and provided r = −0.282, p < 0.01. There is also a positive and significant relation between life satisfaction and social support received r = 0.292, p < 0.01, and social support provided r = 0.409, p < 0.001. There is a positive and significant relation between family satisfaction and social support received r = 0.330, p < 0.01, in the same way as with social support provided r = 0.222, p < 0.05. The regression analysis related to stress levels of parents indicates that social support received predicts levels of stress significantly p < 0.001, with the variable of number of children being the one that showed to be significant p < 0.05. Social support provided showed the most significant results p = 0.001, meaning that social support provided increased life satisfaction. Social support received explains family satisfaction (p = 0.50), as it increases the family satisfaction of parents of children with cancer. Discussion Analysing social support received and provided, as well as sociodemographic and clinical variables, allowed us to broaden the knowledge on the effect social support has on stress levels, life satisfaction and family satisfaction in parents of children and AYAs diagnosed with cancer. This may have relevant practical implications for the design of interventions that would improve parents’ lives.